ChemInform Abstract: Transition‐Metal‐Free Synthesis of Homo‐ and Hetero‐1, 2, 4‐triaryl Benzenes by an Unexpected Base‐Promoted Dearylative Pathway. Issue 44 (13th October 2016) - Rehan, Mohammad; Maity, Sanjay; Morya, Lalit Kumar; Pal, Kaushik; Ghorai, Prasanta
Abstract: An unprecedented approach for the synthesis of homo‐ and heterotriaryl benzenes is developed by using a base‐mediated reaction of either α‐aryl cinnamyl alcohols or α, γ‐diaryl propanones.